Restrukturisasi pembiayaan pada baitul maal wattamwil dilihat dari perspektif maqashidussyariah - Nurjamil, Nurjamil (ARKA INSTITUTE, 2022)
This study was conducted to elaborate further on the restructuring policy carried out by the management of Baitul Maal Wattamwil (BMT) for financing customers who experience Non Performing Financing (NPF) problems due to the impact of Covid 19 Viewed from the Perspective of Maqashidussyariah. This study is a library research using a qualitative descriptive method, where researchers describe data on the impact of Covid 19 on the financing problems of BMT customers which are responded to with a restructuring policy linked to maqashidussyariah. The results of this study state that the restructuring policy is a primary need (dharuriyyah) which can be categorized as an effort to maintain the assets (Hifdzh Al-Maal) of depositors and maintain the honor (Hifdzh Al-‘Irdh) of financing customers. It can be concluded that this is very closely related to the professionalism of the manager and by maintaining the principle of caution and entering the category of maintaining the honor (Hifdzh 'Irdh) of financing customers because the honor of a believer is an obligation for other Muslims.